Unidimensional and Multidimensional Reliability Coefficient of Karmapatha Philosophy-based Student Behavior Questionnaire - Puger, I Gusti Ngurah (Universitas Pendidikan Ganesha, 2024)
Guidance and Counseling teachers often highlight student behavior, especially in Junior High Schools. This is because many junior high school students' behavior contains anomalies compared to the school rules in the student handbook. The purpose of this research is to create a student behavior questionnaire based on the teachings of karmapatha that has a standard when assessed based on the reliability of the questionnaire. This research is a type of instrument calibration research. The population of this study was all students of grade VIII junior high school, with the sample being the answers of 100 students selected by purposive sampling. Data collection methods with tests. The results of data analysis obtained unidimensional reliability, student behavior questionnaire based on karmapatha teachings before being corrected by spurious overlap effect obtained rxx' coefficient of 0.850 meets the feasibility to be used as a research instrument; and when examined from unidimensional reliability, student behavior questionnaire based on karmapatha teachings after being corrected by spurious overlap effect obtained rxx' coefficient of 0.853. Multidimensional reliability, the karmapatha teaching-based student behavior questionnaire, before being corrected by the spurious overlap effect, obtained an αs coefficient of 0.945. and when examined from multidimensional reliability, the karmapatha teaching-based student behavior questionnaire, after being corrected by the spurious overlap effect, obtained an αs coefficient of 0.942, overall meeting the feasibility to be used as a research instrument.